Nocturnal Velvet Ants (Hymenoptera: Mutillidae) of Joshua Tree National Park, Riverside County, California with the description of three new species - Sadler, Emily A.; Pitts, James P.; Wilson, Joseph S. (Zootaxa, 2017)
The diversity of nocturnal velvet ants at Joshua Tree National Park (JTNP) is investigated along with seasonal activity. The diversity of velvet ants found at JTNP is compared to the diversity of velvet ants found at the Algodones Sand Dunes, Philip L. Boyd Deep Canyon Desert Research Center, Ash Meadows National Wildlife Refuge and the Nevada Test Site. Diagnoses and a key are provided for the velvet ants of JTNP. Forty-one species in six genera, based on 10,202 specimens collected from a transect of 14 sampling sites transitioning from the Mojave to the Sonoran deserts, are found to inhabit areas in and around the park. Odontophotopsis dalyi, O. odontoloxia and Photomorphus schoenwerthi are described as new species. Odontophotopsis (Odontophotopsis) ambigua Mickel (1983) is a junior synonym of O. delodonta Viereck (1904), new synonym. The females of too few of the species are known, so only the males are treated. A key to all of the species and illustrations for those species not previously illustrated are provided for the males.